2012
DOI: 10.1155/2012/574656
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adherence to Antiretroviral Therapy among HIV-Infected Patients in Africa

Abstract: Background. There are only a few comprehensive studies of adherence to ART and its challenges in Africa. This paper aims to assess the evidence on the challenges and prospects of ART adherence in sub-Saharan Africa. Methods. The authors reviewed original and review articles involving HIV-positive individuals that measured adherence to ART and its predictors in the past decade. Findings. Against expectations, sub-Saharan Africa patients have similar or higher adherence levels compared to those of developed coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
156
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 79 publications
13
156
4
2
Order By: Relevance
“…The challenges to ART adherence were financial constraints, forgetting to take medication, lack of family care, depression, alcohol use, social stigma and side effects to ART [13,28,32], substance and alcohol abuse [26]. Thus, health care providers must identify possible barriers to adherence at the earliest possible time and provide appropriate solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges to ART adherence were financial constraints, forgetting to take medication, lack of family care, depression, alcohol use, social stigma and side effects to ART [13,28,32], substance and alcohol abuse [26]. Thus, health care providers must identify possible barriers to adherence at the earliest possible time and provide appropriate solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal adherence to antiretroviral drugs (ARV) dosage schedule and timing at a threshold of 95% or more is required to attain an undetectable viral level in infected persons [28,31,34]. Studies have reported the difficulties in attaining optimal adherence as people living with HIV/AIDS tend to miss doses or ignore nutrition recommendation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from various studies across the world have presented different levels of ART adherence, albeit higher in Africa compared to Europe and America [8,28,33]. Similarly, an earlier meta-analysis review of 28 North American and 27 Sub-Sahara African studies reported a pooled ART adherence estimate of 55% for North America and 77% for Sub-Sahara Africa (Mills et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although disparity in access to treatment is undoubtedly a well-documented barrier to treatment, misconceptions and lack of knowledge only compound the problem. 1,2,5,8,9 Limited research from eastern Africa and Ethiopia has suggested that a belief in alternate cures might conflict with adherence to medically necessary treatments. [10][11][12][13] Reasons for default from antiretroviral (ARV) programs in Ethiopia include community pressure and misconception about treatment.…”
Section: Introductionmentioning
confidence: 99%